PENYULUHAN DAN EDUKASI TENTANG KOSMETIK BERBAHAYA DI POSYANDU ZAMRUD - Kumala, Dinna Fitria; Aulia, Hilya; Hadi, Samsul; Isnani, Nazhipah; Fitria, Raudatul (Jurnal Bakti untuk Negeri, 2024)
Cosmetics are a form of preparation intended for the surface of the human body with the aim of fragrant, beautiful, cleansing and protecting the body from external exposure. The great public interest in the use of cosmetics has not been accompanied by a complete understanding of cosmetics. This outreach aims to increase public knowledge about cosmetics and dangerous cosmetics at Posyandu Zamrud. Counseling was held on Wednesday, February 2 2022 at Posyandu Zamrud. This counseling was carried out to 12 people in the community. As a result of this counseling, there was an increase in public understanding with the percentage in the pretest categories of not understanding and not understanding each at 50% to the category of not understanding with a percentage of 8.3% and the understanding category with a percentage of 91.7% in the posttest results.